2011
DOI: 10.1124/jpet.110.177782
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Ameliorates the Susceptibility to Aortic Lesions in a Mouse Model for the Vascular Type of Ehlers-Danlos Syndrome

Abstract: The vascular form of Ehlers-Danlos syndrome (vEDS), a rare disease with grave complications resulting from rupture of major arteries, is caused by mutations of collagen type III [␣1 chain of collagen type III (COL3A1)]. The only, recently proven, preventive strategy consists of the reduction of arterial wall stress by ␤-adrenergic blockers. The heterozygous (HT) Col3a1 knockout mouse has reduced expression of collagen III and recapitulates features of a mild presentation of the disease. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…In grade 4 lesions (Fig. 2D), there was marked and abrupt attenuation of the wall thickness with abundant fibrosis and more severe fragmentation of several elastic laminae (Ramot et al, 2009;Briest et al, 2011). Cooper et al (2010) reported that grade 1 lesions were seen in 55% of studied mice and distributed equally among WT and HT mice of both sexes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In grade 4 lesions (Fig. 2D), there was marked and abrupt attenuation of the wall thickness with abundant fibrosis and more severe fragmentation of several elastic laminae (Ramot et al, 2009;Briest et al, 2011). Cooper et al (2010) reported that grade 1 lesions were seen in 55% of studied mice and distributed equally among WT and HT mice of both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…HT mice used in this study demonstrated previously described characteristics of haploinsufficiency for collagen III: reduced collagen content in aorta, particularly tunica media and increased MMP activity, especially MMP-9 (Cooper et al, 2010;Briest et al, 2011). Two gelatinases, MMP-2 and MMP-9, had been considered functionally similar and important in vascular remodeling, particularly in smooth muscle cell migration and matrix degradation (Yasumitsu et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations